On the oxide films effect on the thermal processes in the particle‐substrate system during plasma spraying - Gromyko, G.; Zayats, G. (Mathematical Modelling and Analysis, 2002)
In the present paper one mathematical model of the thermal processes in the particle‐substrate system under plasma spraying is developed. The energy equation is solved for both particle and substrate regions using the adjoint conditions for the temperature. Main attention is paid to investigation of the temperature in contact of the particle with substrate. The oxide films effect on the surface substrate taking onto account thermal resistance of oxide is simulated. Numerical results for the heat transfer process and the effect of some important processing parameters have been discussed. Numerical algorithms were realized in the form of applied programs complex. Apie plonos plėvelės oksidaciją terminiame poveikyje pagrindinių dalelių sistemoje, kai turime plazminį purškimą Santrauka. Šiame straipsnyje pateikiamas terminių procesų matematinis modelis pagrindinių detalių sistemoje, kai turime plazminį purškimą. Naudojant ribines temperatūros sąlygas abiem dalelėms ir pagrindo sritims išspręsta energijos lygtis. Svarbiausia tyrimų kryptis yra temperatūros poveikyje dalelių sąveika su pagrindu. Modeliuojamas plonos plėvelės oksidacijos poveikis pagrindo paviršiui, atsižvelgiant į šiluminės oksidacijos pasipriešinimą. Išnagrinėtas keleto svarbiu parametrų poveikis šiluminių procesų perdavime. Skaitiniai algoritmai realizuoti panaudojant keletą programų. First Published Online: 14 Oct 2010